Implementasi Vibration Cone Dalam Uji Praktik Pembuatan Sim C Berbsis IoT Dan Website - Dian Susatyono, Jarot; Setiyo Prihatmoko; Febryantahanuji; Daif Naufal Sabih (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
This research aims to develop a motorcycle driving license (SIM C) practical test system using Vibration Cones at SATPAS Purworejo to enhance the accuracy and transparency of assessments previously conducted manually. The primary issue with manual assessment is the high level of examiner subjectivity. The proposed solution involves the implementation of SW-420 vibration sensors integrated with the ESP32 microcontroller. These sensors detect vibrations when a test participant strikes a cone; the data is then transmitted to a server and displayed on a web interface in real-time. This methodology enables objective evaluation based on sensor data. The test results indicate that the Vibration Cone system can detect vibrations with an accuracy rate of 90% and exhibits low data transmission latency under stable network conditions. The system proved reliable across various operational environmental conditions. This study concludes that the implementation of IoT technology in Vibration Cones successfully improves the efficiency, effectiveness, and fairness of the SIM C practical test process at SATPAS Purworejo. This research provides a significant practical contribution to the modernization of data-driven public service systems, reducing potential human error and fraudulent assessment practices.